Compiler-guided leakage optimization for banked scratch-pad memories. - Kandemir, M. (IEEE Transactions on VLSI systems)
Current trends indicate that leakage energy consumption will be an important concern in upcoming process technologies. In this paper, we propose a compiler-based leakage energy optimization strategy for on-chip scratch-pad memories (SPMs). The idea is to divide SPM into banks and use compiler-guided memory-data layout optimization and data migration to maximize SPM bank idleness, thereby increasing the chances of placing banks into a low-power (low-leakage) state. Our experimental results with eight applications show that the proposed compiler-based strategy is very effective in reducing leakage energy of on-chip SPMs.